SOME NUMERICAL ANALYSES ON THE SOLUBILITY OF VANILLIN IN CARBITOL® + WATER SOLVENT MIXTURES (2015)
In this communication some reported solubility values of vanillin (component 3) in 2-(2-ethoxyethoxy)ethanol (Carbitol®, component 1) + water (component 2) mixtures at five temperatures from  298.15 to 318.15 K were correlated with the Jouyban-Acree model combined with van’t Hoff or Apelblat equations, obtaining models in second degree regarding the mixtures compositions. Mean percentage deviations were near to 6.0%. On the other hand, by means of the inverse Kirkwood-Buff integrals it was demonstrated that vanillin is preferentially solvated by water in water-rich mixtures (with a minimum δx1,3 value in the mixture x1 = 0.05, i.e. –4.29 x 10–2) but preferentially solvated by the cosolvent in mixtures with compositions 0.12 x1 1.00 (with a maximum δx1,3 value equal to 3.61 x 10–2 in the mixture x1 = 0.25).  It is conjectural that hydrophobic hydration plays a relevant role in the first case, whereas, in the second case, vanillin would be acting as Lewis acid with Carbitol®.